On the modelling of microsegregation in steels involving thermodynamic databases. Issue 1 (March 2016) - You, D; Bernhard, C; Michelic, S; Wieser, G; Presoly, P
Abstract: A microsegregation model involving thermodynamic database based on Ohnaka's model is proposed. In the model, the thermodynamic database is applied for equilibrium calculation. Multicomponent alloy effects on partition coefficients and equilibrium temperatures are accounted for. Microsegregation and partition coefficients calculated using different databases exhibit significant differences. The segregated concentrations predicted using the optimized database are in good agreement with the measured inter-dendritic concentrations.